The role of agricultural digitization in reducing agricultural carbon emissions: evidence from China - Jianxin Chang (Cogent Food & Agriculture)
Agricultural digitization (AD) is closely integrated with agricultural development and plays an increasingly important role in agricultural carbon emission (ACE) reduction. This study first analyzes the mechanism of AD reducing ACE. Then, based on China’s provincial panel data from 2011 to 2022, a two-way fixed effect model, spatial econometric model, threshold effect model, mediating effect model, and moderating effect model are used to verify the research hypotheses. The main research conclusions include: (1) AD has a significant reduction effect on ACE. (2) Not only does AD reduce ACE in the studied locality province, but AD also has a negative spatial spillover effect on ACE in adjacent geographical provinces. (3) There are double thresholds for agricultural economic development. As AD gradually crosses these two threshold values, the reducing effect of AD on ACE is gradually increasing. (4) Agricultural technology innovation plays a mediating effect in the process of AD reducing ACE. (5) Agricultural human capital plays a moderating effect in the process of AD reducing ACE. Therefore, policy suggestions are proposed to accelerate the construction of agricultural digital infrastructure and deepen integration of AD and agricultural production.